Antimicrobial resistance in Antarctica: Is it still a pristine environment? - Kudzai Hwengwere; Harisree Paramel Nair; Kevin Hughes; Lloyd S. Peck; Mel S. Clark; Caray A. Walker (2022)
Although the rapid spread of antimicrobial resistance (AMR), particularly in relation to clinical settings, is causing concern in many regions of the globe, remote, extreme environments, such as Antarctica, are thought to be relatively free from the negative impact of human activities. In fact, Antarctica is often perceived as the last pristine continent on Earth. Such remote regions, which are assumed to have very low levels of AMR due to limited human activity, represent potential model environments to understand the mechanisms and interactions underpinning the early stages of evolution, de novo development, acquisition and transmission of AMR. Antarctica, with its defined zones of human colonisation (centred around scientific research stations) and large populations of migratory birds and animals, also has great potential with regard to mapping and understanding the spread of early-stage zoonotic interactions. However, to date, studies of AMR in Antarctica are limited. Here, we survey the current literature focussing on the following: i) Dissection of human-introduced AMR versus naturally occurring AMR, based on the premise that multiple drug resistance and resistance to synthetic antibiotics not yet found in nature are the results of human contamination ii) The potential role of endemic wildlife in AMR spread There is clear evidence for greater concentrations of AMR around research stations, and although data show reverse zoonosis of the characteristic human gut bacteria to endemic wildlife, AMR within birds and seals appears to be very low, albeit on limited samplings. Furthermore, areas where there is little, to no, human activity still appear to be free from anthropogenically introduced AMR. However, a comprehensive assessment of AMR levels in Antarctica is virtually impossible on current data due to the wide variation in reporting standards and methodologies used and poor geographical coverage. Thus, future studies should engage directly with policymakers to promote the implementation of continent-wide ...